PENGARUH PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP PENINGKATAN LITERASI LINGKUNGAN DAN PERILAKU RAMAH LINGKUNGAN GREEN BEHAVIOR SISWA SEKOLAH DASAR - Hairul Uyun; Encep Supriana; Ni Made Winursiti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of the implementation of project-based learning models in improving environmental literacy, green behavior, and environmental awareness among third-grade students at SDN Warnasari Elementary School. Through the